Interference system for high pressure environment. (October 2021) - Kumpulainen, Tero; Singh, Amandeep; März, Thomas; Dong, Litong; Reuna, Jarno; Vihinen, Jorma; Li, Dayou; Levänen, Erkki
Highlights: Two interference systems were developed and tested in the high-pressure environment. Interference patterning in liquid, gas and supercritical state was demonstrated. Both systems can be used in the pressurized environment for processing. Abstract: Laser interference patterning or lithography has been used in variety of the applications using, patterning, masking and processing structures at top of material. It offers fast processing over as large areas can be processed simultaneously. Additionally, fine patterns are possible to achieve both in micro and sub-micro scale. In this manuscript is presented novel concept to combine interference patterning and high-pressure processing environment. With aid of high-pressure system, it is possible to control processing environment and add co-solvents in desired state (liquid, gas, supercritical) and use developed system as controlled reactive environment in the future studies. Two systems were developed and assembled for testing and proofing the concept. The results of the two 4-beam interference systems (lens- and mirror-based) are presented and compared.